Evaluation of a novel individualised communication-skills training intervention to improve doctors' confidence and skills in end-of-life communication. (March 2013) - Clayton, Josephine M; Butow, Phyllis N; Waters, Amy; Laidsaar-Powell, Rebekah C; O'Brien, Angela; Boyle, Frances; Back, Anthony L; Arnold, Robert M; Tulsky, James A; Tattersall, Martin HN
Background: We developed a novel individualised training program regarding end-of-life communication, designed to be time effective for busy junior-doctors working in hospital settings. Aim: We aimed to pilot this brief individualised training program with junior-doctors to explore its acceptability, feasibility and effect on the doctors' confidence, communication skills, attitudes towards psychosocial care and burnout. Design: The content of the training intervention was informed by a systematic literature review and evidence-based clinical practice guidelines regarding end-of-life communication. The intervention was based on sound educational principles and involved three one-hour teaching sessions over a three-week period, including two individual sessions with an expert facilitator and simulated patient/caregiver. In addition, participants received written and audiovisual take-home learning materials. Participants were videotaped consulting with a simulated patient/caregiver pre/post training to assess the impact of the course on their communication behaviours. Participants completed de-identified questionnaires pre/post training, including self-assessed confidence, attitudes to psychosocial care, and the Maslach Burnout inventory. Participants: Participants included 22 junior-doctors from a large teaching hospital in Sydney, Australia. Results: All participants reported that the training was useful, had been helpful for their communication with patients and that they would recommend the training to others. Significant improvements were found in participants' communication skills (in seven out of 21 specific and all three global communication behaviours assessed, range P =0.02 to <0.001), confidence in communicating about relevant topics ( P <0.001), attitudes towards psychosocial care ( P =0.03) and sense of personal accomplishment ( P =0.043). There were no overall differences in participants' burnout levels. Conclusion: This intervention shows promise and warrants further formal evaluation.